Unusual accumulation of a-tocopherol in rabbits fed palm-oil diets enhanced with various vitamin E components - Hew, N. F.; Khor, H. T.; Choo, Y. M.; Yap, S. F.; Goh, S. H. (Malaysian Journal of Science (MJS), 1994)
The disü•ibutions of tocopherols and in rabbit plasma and liver were determined by feeding rabbits with various semisynthetic diets containing y-tocotrienol, ô-tocopherol or (1-tocopheryl acetate as the major vitamin E supplement. A high accumulation of a-tocopherol but not the other vitamin E compounds was observed in all groups. The ratios of tocotrienols: tocopherols and 6-tocopherol:ot-tocopherol in the Y-tocotrienol and 6-tocopherol-supplemented diets, respectively, were drastically reduced in the plasma and liver of the rabbits. The low levels of y-tocotrienol and 6-tocopherol were not due to bioconversion to the a-vitamer by the liver from radiotracer study, and may be due to their higher antioxidant reacüvities in combination with the presence of a highly selective (1-tocopherol-binding protein in the liver.